(untitled) (Comprehensive Journal of Science, 2025)
This study tries to shed light on one of the group of problems that modern organizations face in general and health organizations in particular, and it is the problem of low level of service quality, and this study discussed (organizational culture and its impact on the quality of health services), and the problem of the study lies in the existence of a low level Quality of health services provided health care centers in Zawia.Where this study aims to study and characterize the reality of the organizational culture prevailing in health care centers and the extent of its compatibility with the requirements of applying the level of quality of health service provided in these centers, as well as to identify the extent of employees’ awareness of the concept of organizational culture and its impact on the level of quality of health services.This study was based on the following hypothesis (the health centers in Zawia dominate a negative organizational culture that negatively affected the quality of health services provided).The researchers adopted the path of achieving the objectives of the study, and testing the hypothesis of the study, by following the descriptive approach and the analytical method, using the statistical methods included in the statistical package (SPSS).The study population consisted of (471) people distributed in 7 health centers. A stratified random sample was chosen, which was determined by the sample selection law, where the sample amounted to (206) individuals.The study reached a number of results, the most important of which are:1- The prevailing organizational culture among workers in health care centers in Zawia is a negative organizational culture.2- There is a low level of quality of health services provided in health care centers.3- There is a positive (positive) significant relationship between the prevailing organizational culture and the level of quality of health services provided in health care centers, as the more positive the organizational culture, the higher the level of quality of services provided in these centers.4- Lack of awareness among health center workers of the concept of organizational culture.Second - Recommendations:After linking the results with the recommendations, the study recommends some recommendations.1- The need for higher management to pay attention to the organizational culture prevailing among the employees so that this culture is positive, in order to work to achieve the goals of health care centers. 2- The need for administrative leaders to pay attention to selecting and training individuals wanted and transferred to new appointments, which would lead to placing the right person in the right place. 3- Working on developing the capabilities of workers and cultivating honest competition among them.4- Work to raise the quality of health services provided in health care centers and apply quality standards, by providing supportive medical services in an integrated manner to perform the required medical services.5- Paying attention to preparing maintenance programs and providing spare parts for medical devices and equipment, so that these devices work perfectly.6- Working on preparing administrative training courses to spread the concept of organizational culture among workers, to increase workers ’linkage among themselves and achieve high quality services.